A guide book on short case examination in internal medicine for medical undergraduates - Abdul Azih, Muhammad Naimmuddin (IIUM Press, 2019)
Internal Medicine (IM) is a major posting for Bachelor of medicine and Bachelor of Surgery undergraduate program of Internal Islamic University of Malaysia, MBBS (IIUM). In clinical years, the examinations for this posting consists of theory and clinical examinations. The clinical examinations consist of long and short case examinations. This book is intended to serve as a guide to the techniques and knowledge required for short case examination in IM posting. Basically, there are 5 main areas that are covered, namely, cardiovascular, respiratory, abdominal, neurological and other examinations (covering endocrine and rheumatological examinations). To familiarise students with the real examination settings, in each clinical scenario, a series of questions are put forth in the sequence of provisional and differential diagnoses, relevant investigations, final diagnosis (after the main investigation results are revealed), followed by the principles of management. Since, the topics in IM are very broad and at times seems notoriously complicated for medical undergraduates, this guide book is designed as a practical and simple reference. Indeed, it is intended to concisely and comprehensively describe the relevant topics in systematic, consistent and organized manners to help medical undergraduates to learn effectively during their IM postings. Importantly speaking, knowledge in basic medical sciences that was taught in the pre-clinical years is crucial for students to understand this book. Thus, thorough revisions and understanding of anatomy, physiology, pathology and many others pre-clinical subjects is vital. Ultimately, this book requires clinical applications in real practice by the readers in order for them to gain maximum benefits.